(untitled) - Champeaux, Dennis de (Reading, Mass., 1993)
Rather than subscribing to a particular object-oriented method, the authors give instructions on how to put key object-oriented concepts to work in software construction. Many examples, including a full banking system, are developed throughout the book to illustrate the process of object-oriented so.
Keywords: Lập trình hướng đối tượng (Khoa học máy tính),Object-oriented programming (Computer science)